LONGER THE BELT, SHORTER IS THE LIFE SPAN - Awan, Zahid Aslam; Mufti, Waqar A; Shah, Karamat Ali (Journal of Ayub Medical College Abbottabad, 1996)
Five hundred and twenty-one subjects presenting for routine exercise tolerance test had their waist circumference, body mass index (BMI), waist-hip ratio(WHR) and serum cholesterol measured. Compared to weight and body mass index, waist-hip ratio and waist circumference has been found to be better anthropometric predictors of hypercholesterolemia and positive exercise tolerance test. Moreover, an average waist circumference and WHR is high in our population and females are having relatively higher serum cholesterol levels than men.